Comparative Evaluation of Scar Tissue from Chest Tube Wound Closure Using Knotless and Conventional Methods Using the Patient and Observer Scar Assessment Scale - Tangkilisan, Adrian N; Oley, Mendy H; Oley, Maximillian C; Loho, Claudia; Sukanto, Wega; Tamburian, Christha Zenithy; Langi, Fima L.F.G. (UI Scholars Hub, 2023)
Introduction. Chest tube placement is widely practiced; most medical doctors can do this safely. However, releasing the chest tube can be a painful and challenging experience for the patient. A novel method has been developed with a new suture material that does not need to be knotted. The Patient and Observer Scar Assessment Scale (POSAS) provides objective and subjective scar assessment. This study aimed to compare the scars associated with chest tube release between the conventional and knotless methods. Methods. The study was a controlled trial in which patients were divided into two groups. The scar assessment was carried out by the researcher and the patient in the third month after the operation, using POSAS scores. Results. The Mann–Whitney test showed significant differences between the methods in both patient and researcher assessments (p Conclusion. According to POSAS scores, scar tissue formation from the knotless method was more acceptable to patients than the conventional method. Therefore, this can be an alternative method for chest tube wound management.